The binding of poly (rA) and poly (rU) to denatured DNA. II. Studies with natural DNAs. - Mol, J N (1976)
We have studied the interaction of poly(rA) and poly(rU) with natural DNAs containing (dA.dT)n sequences. The results indicate that hybridization of poly(rA) to denatured DNA can be used to estimate the size and frequency of large (dA.dT)n tracts, whereas hybridization with poly(rU) does not give reliable information on these points. In 6.6 M CsCl, poly(rU) can form stable complexes with denatured DNA containing short (dA)n tracts (n less than or equal to 6), whereas binding of poly(rA) to denatured DNA under these conditions requires much larger (dT)n tracts (estimated n greater than 13). Moreover, binding of poly(rA) requires pre-hybridization in low salt, because free poly(rA) precipitates in 6.6 M CsCl.